Effects of replacing fish meal with enzymatic cottonseed protein on the growth performance, immunity, antioxidation, and intestinal health of chinese soft-shelled turtle (Pelodiscus sinensis) - Qiu, Zongsheng; Zhao, Jiantao; Xie, Dazhang; de Cruz, Clement R.; Zhao, Jianhua; Xu, Hong; Xu, Qiyou (Wiley, 2023)
The dietary effects of replacing fish meal with enzymatic cottonseed protein (ECP) on the growth performance, immunity, antioxidant, and intestinal health of Chinese soft-shelled turtles have not been explored. An eight-week feeding trial was conducted with a quadruplicated group of turtles (3:44 ± 0:01 g) that were randomly assigned to 16 cages (0:6m—0:6m—0:6 m) with 30 turtles that were stocked in each cage. Four dietary groups were fed with diets supplemented with 0, 2, 4, and 6 (ECP0 group (control group), ECP2 group, ECP4 group, ECP6 group) of enzymatic cottonseed protein replacing fishmeal. The present study illustrated that the final weight and WG in the ECP2 and ECP4 groups were significantly increased (P < 0:05) compared with the control group. The ECP2, ECP4, and ECP6 groups significantly reduced the feed coefficient (P < 0:05) and significantly increased the SGR (P < 0:05). The serum TP and ALB of the ECP4 group were significantly increased (P < 0:05). The ECP2, ECP4, and ECP6 groups significantly increased the activity of intestinal pepsin (P < 0:05), and the activity of intestinal lipase of the EPC4 group was significantly increased (P < 0:05). The intestinal villus height of the EPC4 group and EPC6 group, the villus width of the EPC2 group and EPC4 group, and the intestinal muscle thickness of the EPC4 group were significantly increased (P < 0:05). At the same time, replacing fishmeal with enzymatic cottonseed protein also affected the intestinal inflammation-related genes compared with the control group. Besides that, the expression of the IL-10 gene in the experimental group was significantly upregulated (P < 0:05). Nevertheless, the expression of TNF-± and IL-8 genes in the ECP2 group and TNF-± and IL-1² genes in the ECP4 group was significantly downregulated (P < 0:05). In summary, replacing fish meal with enzymatic cottonseed protein positively affects the growth, immunity, and intestinal health of Chinese soft-shelled turtles. The appropriate proportion of enzymatic cottonseed protein to replace fish meal in turtle feed is 4.